Dari Epos ke Resistensi - Otong Sulaeman; Dani Nur Pajar; Ayu Lestari (Indonesia Center for Middle East Studies, 2026)
This article examines the relationship between Persian literary memory and the formation of the narrative of modern Iranian resistance amid global geopolitical pressures. So far, Iran's resilience has more often been explained through military factors, state ideology, and geopolitical strategy, while the cultural-civilizational dimension has received relatively little attention in contemporary Iranian studies. This study seeks to answer the question of how the Persian literary tradition, especially Ferdowsi's Shahnameh epic, contributes to the formation of the collective identity and psychological resilience of modern Iranian society. This study uses a historical-interpretive approach to understand the relationship between the classical Persian literary tradition and the formation of modern Iranian political identity. The results show that Shahnameh serves not only as a classic post-Islamic literary work, but also as a symbolic archive that reproduces the values of heroism, dignity, sacrifice, and resistance in the contemporary Iranian political imagination. The study also shows that the resilience of modern Iran was formed through the interaction between the memory of Persian civilization and Shia political theology. This article contributes to the development of the study of cultural geopolitics and civilizational resilience in contemporary Middle East studies.